Continuous Drip Flow System to Develop Biofilm of E. faecalis under Anaerobic Conditions - Ana Maria Gonzalez; Erika Corpus; Amaury Pozos-Guillen; Daniel Silva-Herzog; Antonio Aragon-Piña; Nestor Cohenca (The Scientific World Journal)
Purpose. To evaluate a structurally mature E. faecalis biofilm developed under anaerobic/dynamic conditions in an in vitro system. Methods. An experimental device was developed using a continuous drip flow system designed to develop biofilm under anaerobic conditions. The inoculum was replaced every 24 hours with a fresh growth medium for up to 10 days to feed the system. Gram staining was done every 24 hours to control the microorganism purity. Biofilms developed under the system were evaluated under the scanning electron microscope (SEM). Results. SEM micrographs demonstrated mushroom-shaped structures, corresponding to a mature E. faecalis biofilm. In the mature biofilm bacterial cells are totally encased in a polymeric extracellular matrix. Conclusions. The proposed in vitro system model provides an additional useful tool to study the biofilm concept in endodontic microbiology, allowing for a better understanding of persistent root canal infections.